Resonanzräume der Gewaltkriminalität: zwei rechtsextremistische Gruppen im Vergleich - Mletzko, Matthias (2013)
Abstract: The fact that the German right-wing terrorist group „NSU“ could operate for over ten years without even being identified shows serious analytical deficiencies, not only in the sphere of security agencies but in the field of academic research. One of the identified failures was an insufficient analysis of specifics and intensities of right-wing extremist violence and hate-driven attitude. The following text tries to fill some of the gaps, by means of comparing two violent right-wing extremist groups that operated in the federal state of Saxony from the end of the 90ies through the first half of the following decade. It elaborates patterns of violence and ideological, hate-driven attitude. The comparison is part of an ongoing HAIT-research project focussing on right-wing militants with intensive violent behavior and the groups by which they organise themselves (authors abstract)